Cost and Time Performance Evaluation of a Sports Hall Construction Project Using the Earned Value Method: A Case Study at Gunung Kidul Campus, Universitas Negeri Yogyakarta - Pratiwi, Anik Nurul; Prihadi, Wisnu Rachmad; Al-Pashya, Muhammad Donny Reval (Universitas Negeri Yogyakarta, 2025)
The main objectives in managing construction work involve controlling costs, ensuring quality, and meeting project deadlines. Construction projects are regarded as successful when they deliver outputs that satisfy predefined quality standards, are finished on time, and stay within the agreed budget. The Earned Value Method (EVM) is a valuable technique in project management for assessing both cost efficiency and schedule adherence throughout the project’s duration. Important indicators for this analysis include BCWP (Budgeted Cost of Work Performed), BCWS (Budgeted Cost of Work Scheduled), ACWP (Actual Cost of Work Performed), Schedule Variance (SV), Cost Variance (CV), Schedule Performance Index (SPI), Cost Performance Index (CPI), Estimated At Schedule (EAS), and Estimated Temporary Schedule (ETS). This research focuses on evaluating the performance of the Sports Hall Building construction project at Gunung Kidul Campus by applying the earned value method. The assessment emphasizes time scheduling and cost management to gauge how well the project progresses relative to its planned schedule and budget. The study’s findings reveal the current condition of both cost and schedule aspects of the Sports Hall Building project at Gunungkidul Campus, Universitas Negeri Yogyakarta. The data showed a positive cost variance, indicating that the project’s actual expenditures were less than originally planned.